Effectiveness of relaxation techniques, touch distractions in lowering pain scales - Yefta Primasari; Mery Kana (Jurnal Edukasi Ilmiah Kesehatan, 2024)
Introduction: Pain is one of the most common symptoms experienced by patients with various medical conditions. Effective pain management is essential to improve a patient's quality of life. Relaxation and touch techniques are nonpharmacological methods that can reduce Pain. This study evaluated the effectiveness of relaxation and touch techniques in lowering pain scales. Methods: This study used an experimental design with pre-test and post-test approaches. Patients with chronic pain were divided into two groups: an intervention group that received relaxation and touch techniques and a control group that did not receive an intervention. Relaxation techniques used include deep breathing, meditation, and progressive muscle relaxation. The touch techniques used are massage and therapeutic touch. The pain scale was measured using the Visual Analog Scale (VAS) before and after the intervention. Results: The management of relaxation techniques and touch distraction patients on the first- and second-days experienced changes in pain scales, but the Pain was not resolved. On the third day, the Pain was also not resolved if hyperlipidemia pressure increased, while the first day and day two experienced changes in pain scale but were not resolved, and on the third day, the Pain could be resolved with a pain scale of 0. Conclusions: Relaxation and touch techniques effectively lower pain scales in patients with chronic Pain. This method can be part of comprehensive pain management to improve a patient's quality of life. Both techniques can be used as additional methods in pain management to improve a patient's quality of life. Further studies with larger samples and extended intervention periods are needed to confirm these findings. Relaxation and touch techniques can be integrated into clinical practice as part of a multimodal approach to pain management. Education and training for health workers on the use of these techniques can improve patient acceptance and adherence.